OCCULT MOSAICISM OF KARYOTYPING IN 45,X / 46,XY DSD - Shahidan, Nurul Ain Shahirah; Tan, Per Ru; Teoh, Sze Teik (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Disorder of sex development (DSD) with 45,X/46,XY mosaicism is a rare disorder. The prevalence is estimated to be less than 1:20,000. CASE A term baby, born with a good Apgar score at Hospital Sultan Abdul Halim. Genital examination showed atypical appearance with genital tubercle measuring 1.8 cm, bilateral labio-scrotal folds partially fused with single opening at perineum and no palpable gonads. External genitalia score (EGS) was 5/12. Ultrasound assessment revealed right inguinal lesion, equivocal for testis or inguinal hernia and small fluid-filled tubular structure posterior to the bladder which could represent either vagina or urogenital sinus. Genitogram report was consistent with vagina and complementary visualization of the uterus. Salt wasting was not observed during NICU stay. A 17-OHP screen on day-7-of-life reported 41.7 nmol/L. Urgent karyotyping initially reported 46,XY (cells analyzed 18, counted 10). On further assessment at the Hospital Sultanah Bahiyah, hormonal profile showed elevated gonadotrophins (FSH: 112.8 IU/L, LH: 2.74 IU/L and testosterone: 8.07 nmol/L). Follow-up 17-OHP was 82.8 nmol/L, and a short Synacthen test showed peak cortisol measuring 863.6 nmol/L. Serum AMH was 19.2 nmol/L (NV: 235.5–1125.9 for males and ≤31.2 for females). HCG stimulation showed increased testosterone: 2.00 nmol/L (Day 1) and 8.4 nmol/L (Day 3). Secondary analysis of initial chromosome samples with 48 cells analyzed and 15 counted [total 63], revealed mosaicism 45,X [14], 46,XY [49]. Surgical evaluation by 1-year-old reported presence of uterus with left streak gonad (removed) and right fimbriae-like-structure (biopsy) and suspected ovotestes (2 x 2 cm). HPE results are still pending by the time of report. CONCLUSION Chromosomal analysis with adequate cells is crucial in identifying subtypes of DSD. When mosaicism is suspected, a larger number of cells (at least 30) should be analyzed to accurately detect and characterize these conditions.